Al-I'tiraf as a Representation of Repentance and Spirituality in Classical Islamic Literature - Ekayani, Ridha; Sudjatnika, Tenny (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The poem Al-I'tiraf by Abu Nawas is a poem with the theme of repentance that has been widely recognized and sung by Muslims across generations. However, the poem Al-I'tiraf is not just a poem of repentance, but also a document of civilization that reveals the dynamics between religious norms and freedom of expression. This study focuses on a brief introduction to Abu Nawas himself, the role of poets in the Abbasid era, linguistic and rhetorical analysis, religious norms and freedom of expression in this poem, and the humanist values contained therein. The study will examine how these elements can be combined effectively in the poem, and how these elements can have a strong influence on the emotions of the readers or listeners of the poem.